Characterization of lacZ Complementation Deletions Using Membrane Receptor Dimerization. (February 2003) - Thormeyer, D.; Ammerpohl, O.; Larsson, O.; Xu, Y.; Asinger, A.; Wahlestedt, C.; Liang, Z.
We describe the screening of lacZ deletions in mammalian cells and the discovery of a novel pair of lacZ deletions that can undergo α-complementation only when they are fused to peptides that interact with each other. The two lacZ deletions, ΔN 11-75 and ΔC 82-1023, were first characterized by fusing to two small interacting peptides and were then further analyzed by fusing to three membrane receptors (G protein-coupled receptors α2c AR and D2DRL and receptor tyrosine kinase insulin receptor) that were known to form homodimers in the membrane. Histochemical and quantitative FACS ® assays demonstrated that the novel deletions have much lower level of association with each other, thus offering a much lower background in monitoring membrane protein interactions compared to previously published lacZ deletions. Furthermore, our method has the exciting potential to monitor simultaneously membrane receptor dimerization and localization to the cell surface of living cells.